ANALISIS PENERAPAN E-FILLING SEBAGAI UPAYA PENINGKATAN KEPATUHAN WAJIB PAJAK BADAN DALAM PENYAMPAIAN SPT TAHUNAN WAJIB PAJAK BADAN DI KPP PRATAMA PANDEGLANG - Mohamad Husni; Susi Susanti (Universitas Serang Raya, 2018)
In realizing modern tax administration system that the government provide an application that can be used for charging the taxpayer, reporting notification letter (SPT) is precise, fast, and secure. The purpose of this study was to analyze the implementation of e- filing as an effort to increase tax compliance in the delivery of a notice (SPT) Annual taxpayer on STO Pandeglang.This study used a qualitative approach, by conducting a case study. by analyzing and understanding the issues related to tax compliance in the submission of their annual tax return taxpayer, analyze, investigate, and determine conclusions. Results of research showed there are some findings that an increase in the delivery of a notice (SPT) in 2015 and increased taxpayer compliance rate in 2015. It can be concluded that the implementation of e-filing can improve taxpayer compliance in the submission of annual returns taxpayers in KPP PRATAMA PANDEGLANG.